2011
DOI: 10.1099/vir.0.030361-0
|View full text |Cite
|
Sign up to set email alerts
|

Recombination analysis of intermediate human adenovirus type 53 in Japan by complete genome sequence

Abstract: Human adenovirus type 53 (HAdV-53) has commonly been detected in samples from epidemic keratoconjunctivitis (EKC) patients in Japan since 1996. HAdV-53 is an intermediate virus, containing hexon-chimeric, penton base and fiber structures similar to HAdV-22 and -37, HAdV-37 and HAdV-8, respectively. HAdV-53-like intermediate strains were first isolated from EKC samples in Japan in the 1980s. Here, the complete genome sequences of three such HAdV-53-like intermediate strains (870006C, 880249C and 890357C) and fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 34 publications
2
36
0
Order By: Relevance
“…Recently, whole-genome analysis of HAdVs has shown that serum neutralization, by relying on a small fraction of the viral genome as a means of virus identification, can be misleading (21,27,28). For example, HAdV-D53 isolates were originally mistyped as HAdV-D8, -D22, or -D37 on the basis of serum neutralization or limited sequencing (7).…”
mentioning
confidence: 99%
“…Recently, whole-genome analysis of HAdVs has shown that serum neutralization, by relying on a small fraction of the viral genome as a means of virus identification, can be misleading (21,27,28). For example, HAdV-D53 isolates were originally mistyped as HAdV-D8, -D22, or -D37 on the basis of serum neutralization or limited sequencing (7).…”
mentioning
confidence: 99%
“…Among these putative parents of HAdV_Chiba_ E086/2012, only HAdV-22 has been previously clinically reported in ocular infections (30) and it has also been suggested to be a putative recombination parent of HAdV-GT53 (31) and its variants (32,33), which were all isolated from epidemic keratoconjunctivitis patients. Although originally isolated from a respiratory infection, an experimental study has suggested that HAdV-GT60 may have a potential corneal tropism (34).…”
Section: Discussionmentioning
confidence: 99%
“…A lot of new genotypes of HAdV-D, which were defined in this report as the HAdV genotypes without serological determinations, that is those from type number 53 onward, have been recently reported and characterized in terms of evolution and neutralization assays, e.g., HAdV genotype 53 (HAdV-GT53) (2) and HAdV-GT64 (3) (abbreviated as HAdV-GT53 and so on for such genotypes in this report). Except for a few types, such as HAdV-GT54, most of the new genotypes have been suggested to be originated from recombination between the types which were designated by serological typing criteria, i.e., HAdV-1 to 51, particularly in the penton base, hexon and fiber genes (2)(3)(4). It has also been speculated that recombinant viruses exhibiting similar phenotypes to their original viruses (e.g., in tropism and pathogenesis) would have been recognized as known types (3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…The vast majority require nested, multiplex, or multiple singleplex PCRs for the detection of multiple virus types. Furthermore, it is unknown if any of these assays are capable of detecting the newly described HAdV types 53 to 57, responsible for human outbreaks in Japan (13,16,18), China (33), France (27), and the United States (14).…”
Section: Discussionmentioning
confidence: 99%